Analytical Method for 53 Insecticide Residues in Rice Samples - ศิริธรรม, ชรินรัตน์; เกียรตินิติประวัติ , พัชราภรณ์; สีลวานิช , อติชาต; ศิริปี , อรุณี (Journal of Health Science of Thailand, 2025)
Rice is one of the major agricultural exports of Thailand. In the year 2017-2022 the average total rice produced was 25.6 million tons in the year. There are important parameters that determine the quality of rice. One important factor that determines the quality of rice is by setting the limit the maximum contamination level of insecticide in rice. Thus, reliable analysis method is required for insecticide residual determination in rice. The objective is to develop and validate of analytical method for the determination 53 insecticide residues in rice using GC-FPD-µECD method. This method need to be performed in order to fulfill the requirement ISO/IEC 17025:2017. The method was developed during October 2019 and February 2020 for 53 insecticide residue in rice including organochlorine, organophosphorus and systhetic pyrethroids. For this dispersive solid phase extraction method was used in the extraction step before analysis with the GC-FPD-µECD. The method showed linearity in the range of 10-100 ng/mL OCs 50-200 ng/mL for OPs and SPs, respectively (R2>0.9900). The limit of detection for OCs was 0.03 mg/kg and 0.05 mg/kg for OPs and SPs and the limit of quantitation was 0.10 mg/kg for all three groups of insecticides. The accuracy (%recovery) showed in the range from 83 and 109 and with precision as HORRAT in the acceptable range. Therefore, the develop method for 53 insecticide residues detection was very accurate, precise, reliable and was as per the accreditation by ISO/IEC 17025:2017. The developed and validated method was applied for testing rice samples at Regional Medical Science Center 10, Ubon Ratchathani.